Поліфункціональність діяльності як потенційна технологія розвитку організацій - Стахурська, Світлана Антонівна (My University, 2024)
У статті досліджується спрямування та багатофункціональність діяльності організацій в процесі їх розвитку. Незаперечна потреба розвитку та практичні здобутки підприємців в цьому напрямку призвели до накопичення певного масиву інформації, який підлягає узагальненню, систематизації, формуванню методичних підходів щодо забезпечення поступальних процесів розвитку. Для організацій є потреба в створенні алгоритмів, які б пов’язували в єдиній системі процес розвитку та поетапне застосування управлінських підходів до нього, зокрема технологій розвитку. Традиційно процес розвитку відбувався із започаткування діяльності і поступово прямував до укрупнення структури бізнесу. Нині цей процес продовжується в напрямку структурно-операційної оптимізації (зокрема йдеться про аутсорсинґ комерційно перспективних продуктів ) та різноспрямованої колаборації (галузевої, зі «спорідненими» стейкхолдерами, із залученням «нетипових» стейкхолдерів), що призводить до поліфункціональності діяльності

The article examines the direction and multifunctionality of the activities of organizations in the process of their development. The undeniable need for development and the practical achievements of entrepreneurs in this direction led to the accumulation of a certain mass of information, which is subject to generalization, systematization, and the formation of methodological approaches to ensure progressive development processes and their possible differentiation and potential prospects. Development management technologies are considered as a set of methods, methods and tools of management influence on the system and individual subsystems of the organization for the implementation of a certain model of enterprise (organization) development. The systematization of development technologies allows them to be conditionally grouped from the point of view of humanitarian, engineering and empirical approaches. Usually, the use of management technologies allows solving individual problems faced by entrepreneurs on the trajectory of their development. Such technologies are obviously the first project approach, as well as business process reengineering (BPR), total quality management (TQM), knowledge management, evolutionary approaches (the concept of the life cycle of the organization), benchmarking, budgeting, strategic planning, customer segmentation, system customer interaction management, key competencies, process-oriented management, outsourcing, insourcing, scenario planning, balanced scorecard, etc. For organizations, there is a need to create algorithms that would connect the development process and the step-by-step application of management approaches to it, including development technologies, in a single system. Traditionally, the development process took place from the start of activity (business) and gradually progressed to consolidation of the business structure. Currently, this process continues in the direction of structural and operational optimization (in particular, we are talking about the outsourcing of commercially promising products) and multidirectional collaboration (industry, with "related" stakeholders, with the involvement of "atypical" stakeholders), which leads to multifunctionality of activity
Keywords: розвиток організацій; управління розвитком; технології розвитку організацій; поліфункціональність діяльності; структурно-операційна оптимізація; різноспрямована колаборація; комплексний системний розвиток; development of organizations; management of development; technologies of development of organizations; multifunctionality of activity; structural and operational optimization; multidirectional collaboration; complex system development; кафедра економіки праці та менеджменту